Chelation of Thallium by 1,2-Diethyl-3-hydroxy-4-pyridinone in Rats - FATEMI, S.J.; AMIRI, A.; BAGHIZADEH, A.; TORKZADEH, M. (Asian Journal of Chemistry, 2010)
Thallium was introduced to several groups of weanling male wistar rats by act of drinking and feeding. After a period of 35 d, all the rats administered thallium were severely anaemic and showed toxicity symptoms through loss of hair, and increased thallium and decreased iron levels in blood. Chelation therapy was chosen to remove the toxic element from the body. The ability of 1,2-diethyl-3-hydroxy-4- pyridinone chelating ligand in removing thallium was investigated by use of this chelating ligand for one week to the remaining rats of similar groups. The results showed that the thallium level present in blood was significantly reduced and at the same time, the iron concentration returned to a normal level. It was concluded that 1,2-diethyl-3-hydroxy- 4-pyridinone chelating ligand is able to remove thallium from the body and could be used for the treatment of complications and eradication of symptoms of thallium intoxification.